Gingivectomy And Gingivoplasty Combined With Low Dose Doxycicline For Treatment Of Inflammed Fibromatous Epulis In Anterior Gingival Of Maxilla ( Case Report ) - Firmantini, Herrina (Bhakta Dental Journal, 2024)
Background: The Periodontopathogen bacteria is the main etiology of periodontal disease such an fibromatous epulis. Epulis is such a gingival hyperplasia (tumor-like) that came from connective tissue of periodontal. It can caused by Periodontopathogen bacteria and aggravated by a local irritation that occur in long period. The inflammation process made the epulis getting bigger and painfull sometimes. Patient feels unconfidence with this lump mean while the epulis getting bigger. On the other hand, there is some halitosis and uncomfort feeling during chewing and speaking regarding to the epulis. Epulis that grows on the anterior maxilla area can be inconvenient because it became an aesthetics problem and also disrupts the function of the mastication system. Therefore, it has to be completely removed by surgery and some host immunomodulation to eliminate the inflammation and collagenases activity. Case Report: A 44-year-old male patient presented with a chief complaint of a lump on the gum of the anterior teeth on his upper jaw that made him unconfident to smile, difficulties in chewing and speaking. The lump consistency is dense and chewy, bleeds easily, had been there for 3 years. Panoramic reveal a slight bone resorption at the right maxillary second incisor. Case Management : Gingivectomy and gingivoplasty procedures has been done to correct the condition of epulis which is excision and gingival contouring for aesthetic need and Followed with host immunomodulation therapy by using 20 mg low dose doxycicline twice a day for 14 days. Discussion : The condition of epulis can be corrected by gingivectomy and gingivoplasty procedure also by removing the main cause of the epulis (sub-gingival calculus). The aesthetic result can be obtained by gingival contouring after the excision. Host modulation theraphy been given to the patient by using low dose doxycycline for eliminating collagenases activity and breaking the inflammation process in gingiva in order to stop the epulis relapsed. This 20 mg dose of Doxy prevented the elevation of the pro-inflammatory enzyme COX-2 and its downstream product PGE2, which is a potent inflammatory mediator. Conclusion : periodontal surgery treatment need to be followed by certain therapy such as host modulation therapy for gaining successful treatment of periodontal diseases. Keywords : Epulis Fibromatous, inflammation, low dose doxycycline